Pathogenesis, Clinical Presentations and Diagnosis of IgG4-related Disease: AReview - Rahman, Perdana Aditya (Indonesian Rheumatology Associantion, 2021)
IgG4-Related Disease (IgG4RD) was identified by the International Classification ofDiseases (ICD) in 2012. Numerous diseases, including Mikulicz’s disease, Kuttner’stumor, Riedel’s thyroiditis, and Ormond’s disease, are pathologically associatedwith IgG4. Here, we present a review of the clinical presentation and pathogenesisof IgG4-associated disease. IgG4-RD term has been used to refer to a group ofdiseases involving multiple organs in which there is an abundant IgG4-positivelymphoplasmacytic infiltration, storiform fibrosis, obliterative phlebitis, and mildto moderate tissue eosinophilia, all of which show clinically as a tumefactive lesion,usually in more than one organ. IgG4 exhibits a unique property called an unstabledisulfide bond between its heavy chain, as described by Fab-arm exchange whichenables the recombination of a single IgG4 heavy chain with other IgG4 heavychains, resulting in a bispecific antibody incapable of cross-linking and thus offorming an immune complex. IgG4-RD pathomechanism that causes serum IgG4increase and tissue IgG4-plasma-cell deposition that is pathogenic, rather than theIgG4 itself. Genetic predisposition, autoimmunity, T-cell dysregulation, infection,and dysbiosis are just a few of the underlying pathomechanisms. Clinicalsymptoms are also frequently complex and may involve many organs. Confirmationof a diagnosis required a comprehensive anamnesis and examination.